(untitled) (Research, Society and Development, 2021)
Objective: to analyze the evidence available in the literature on the main results of the COVID-19 pandemic on child health. Method: integrative review conducted from January to April 2021 through the search for studies published in 2020 in journals indexed in PubMed/MEDLINE, LILACS and Web of Sciense. Results: the sample consisted of ten primary studies, published in 2020 mainly in English and carried out in Spain and China. The articles that made up the study sample were systematized and presented from the perspectives of Mental, Physical and Social Health. Conclusion: Problems in your physical and mental health, involving changes in behavior, anxiety, obesity and sedentary lifestyle. It makes the creation of strategies for COVID-19’s return to the post-pandemic world indispensable.